2013
DOI: 10.1088/0268-1242/28/3/035011
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-cascade lasers as local oscillators for heterodyne spectrometers in the spectral range around 4.745 THz

Abstract: Local oscillators in terahertz heterodyne spectrometers have to be operated in continuous-wave mode at precisely defined target frequencies. In particular, for advanced airborne instruments, several specifications such as operating temperature and cooling requirements are necessary to be considered. We have developed a quantum-cascade laser (QCL) applicable as a local oscillator for heterodyne spectroscopy of the OI line at 4.745 THz, which is of particular interest for astronomy. We demonstrate a distributed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…One of the desired target frequencies is 4.745 THz in order to execute heterodyne astrophysical measurements of the [OI] cooling line. 3,[9][10][11] Initial works in this research field have been carried out exploiting either first order or third order distributed feedback (DFB) cavities, [12][13][14] which has also lead to device that has been applied in astrophysics measurements. 15 However, compared to these devices, we propose an approach that has the advantage of avoiding any risky cleaving, preserving a surface emission with a single-lobe far field pattern, peak output power of almost 2 mW, low dissipation and single modality with high reliability on the yield of the fabrication process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the desired target frequencies is 4.745 THz in order to execute heterodyne astrophysical measurements of the [OI] cooling line. 3,[9][10][11] Initial works in this research field have been carried out exploiting either first order or third order distributed feedback (DFB) cavities, [12][13][14] which has also lead to device that has been applied in astrophysics measurements. 15 However, compared to these devices, we propose an approach that has the advantage of avoiding any risky cleaving, preserving a surface emission with a single-lobe far field pattern, peak output power of almost 2 mW, low dissipation and single modality with high reliability on the yield of the fabrication process.…”
mentioning
confidence: 99%
“…The easiness of scalability represents an advantage compared to the standard Master Oscillator-Power Amplifier (MOPA) devices, for which the single modality is strictly dependent on the effectiveness of the anti-reflection coating and thus on the target wavelength. 22 The electromagnetic field is out-coupled through a patch antenna that achieves surface emission in a single lobe pattern and it also has the advantage of avoiding cleaving procedures, 12,16,23 exploiting the metal-dielectric-metal optical properties. 24 Finally, as a double metal waveguide composes the laser, not only the heat dissipation is higher than for a single plasmon ridge, but the RC constant of the device is also lower.…”
mentioning
confidence: 99%
“…The carrier injection into the upper laser state is assisted by a transition resonant to the longitudinal optical phonon energy. This reduces thermal backfilling of the lower laser level as well as the principal reabsorption due to electrons in the injector state [17].…”
Section: A Quantum-cascade Laser (Qcl)mentioning
confidence: 99%
“…This design results in operating electrical field strength between 4.5 and 6.5 kV/cm. The low operating voltage and the low current density (400 to 600 A/cm ) result in electrical input powers below 7 W [17]. Fig.…”
Section: A Quantum-cascade Laser (Qcl)mentioning
confidence: 99%
“…In the operation frequency range of the state-of-art THz QCLs, 4.745 THz is close to the highest operation frequency of these devices (5.4 THz) [12]. Unlike around 3 THz where QCL performance peaks and a number of studies have been reported [13], there are few reports in the higher frequency region [10,12,14,15]. Here we exploit THz QCLs operating around 4.6-4.8 THz for application to local oscillators in the heterodyne spectrometer.…”
mentioning
confidence: 95%